Pengubahsuaian Bentuk. Selang Kecerunan Dalam Kaedah Newton bagi Suatu Kelas Fungsi Satu Pembolehubah - Mohd, Ismail (1988)
Improved forms of some interval Newton methods which are described by Hansen (Hansen, 1978b) for computing and bounding the zeros of f"R I ~ R! are given. In order to improve the convergence properties of the methods, the nested form has been used for computing and bounding the derivative f': R I - RI.